If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2x + -4) = 8x Reorder the terms: -5(-4 + 2x) = 8x (-4 * -5 + 2x * -5) = 8x (20 + -10x) = 8x Solving 20 + -10x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 20 + -10x + -8x = 8x + -8x Combine like terms: -10x + -8x = -18x 20 + -18x = 8x + -8x Combine like terms: 8x + -8x = 0 20 + -18x = 0 Add '-20' to each side of the equation. 20 + -20 + -18x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -18x = 0 + -20 -18x = 0 + -20 Combine like terms: 0 + -20 = -20 -18x = -20 Divide each side by '-18'. x = 1.111111111 Simplifying x = 1.111111111
| 2n^2+4n-70=0 | | 5a+3=4+a | | 4(36)+9y=36 | | 6x^2-3x-2=0 | | 2(2x-5)=3(x-2) | | 7y^3-28y=0 | | 2/3a-11=4+a | | 5M-1=-70-151 | | (9x-2)(7x+3)= | | 8n-3=13 | | (10q-3)(q+11)=0 | | 4x+9(36)=36 | | 4=39-9y | | 12=6+2n | | 3(2x-1)+(x-3)=0 | | x(x-9)=15 | | 8=2x-5 | | 6x-75x=100 | | (3q-2)(q-7)=0 | | 3/7x=21 | | 4x^2-44x+112= | | (3p-2)(q-7)=0 | | 1/7/8/9 | | 3x+35x=76 | | 12x=2x | | -2+1=3x-5 | | 2/5h-7=12/5h-2h | | w+1/5=7/8 | | (9p-4)(p+9)=0 | | 8=4m-4 | | 4+(-3/5)x=16 | | n/0.6=662/3 |